Student’s Critical Thinking towards Reading Comprehension using Revised Bloom’s Taxonomy - Melati, Sela Eka; Rasyid, Fathor (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2023)
Critical thinking skills are one of the aims of teaching-learning activities proposed by the Ministry of Education through the implemented curriculum in Indonesia called the 2013 curriculum.   It is a student's ability of cognitive skill divided into two stages of thinking, specifically Low Order Thinking Skill and High Order Thinking Skill. The Critical thinking scheme used in this research, was revised from Bloom’s taxonomy proposed by Anderson (2001). This study used a qualitative descriptive design. The data collected through observations. The instrument of this research used an observation sheet written from the breakdown of the class activities. F, the descriptive qualitative method used to analyze the data. The researcher connected the existing data with the theoretical framework in Revised Bloom’s Taxonomy to interpret the findings in the research data and conclude the final results of the study. Data analysis on teachers’ questioning activities in the classroom shows that the implementation of critical thinking divided into three stages of high-order thinking skills based on Revised Bloom’s Taxonomy. The most used in the teachers’ questioning activities based on the data shows that ten questions frequently used as the question process included the highest stage of thinking or create stage or C6.  On the other hand, the second higher places by analyzing staged or C4 showed six questions. In addition, the other five questions are placed by evaluate stage or C5 based on the Revised Bloom’s Taxonomy.